Prevalence of Tonsillitis caused by Streptococcus spp. Among children and the effect of some Lactic acid bacterial (LAB) strain on it (Baghdad Science Journal, 2016)
In this study 100 samples were collected from infected children with acute and chronic tonsillitis who attended to Al-Yarmook Teaching Hospital (ENT consultation clinic) from 5/12/2013 to 1/3/2014. The result of laboratory culture was positive in 67 samples. Depending on their cultural, morphological and biochemical characterization of bacterial isolate of them were identified as (37.31%) belonged to Streptococcus pyogenes and the diagnosis is confirmed by the use of Remel Rapid STR System, (34.32%) belonged to S.parasanguinis, (11.94%) S.mitis, (11.94%) S.oralis and (4.47%) S.thoraltensis . Results confirmed that cup assay gave highest inhibition zone after 24 hrs compare with well diffusion methods for suspension of L.acidophilus gave highest inhibition zone after 48 hrs for incubation, while ahigh inhibition zone revealed for suspension of L.fermentum after 24 hrs incubation. the study included also the measurement of the inhibition activity for bacteriocins produced by L.acidophilus bacteria against pathogenic bacteria on nutrient agar by well diffusion method in which results revealed stability of the bacteriocins produced towards PH which kept its activity with PH 4-6 for 24 hrs, and the highest stability was with PH 4, however it lost a lot of its activity with acidic PH less than 2 and alkaline PH as 8. The treatment of bacteriocins with salts such as Nacl it revealed little effect in inhibition zone within 1 & 2% concetrations. The salt MgSo4 & Kcl showed reduction in the inhibitory activity in the low concentration, however the higher concentration of salt caused great reduction and 5% concentration led to loss of inhibitory activity for bacteriocins completely.